The Contributions of Model Studies for Fundamental Understanding of Polymer Mechanochemistry - O’Neill, Robert T.; Boulatov, Roman (Synlett, 2022)
The exciting field of polymer mechanochemistry has made great empirical progress in discovering reactions in which a stretching force accelerates scission of strained bonds using single molecule force spectroscopy and ultrasonication experiments. Understanding why these reactions happen, i.e., the fundamental physical processes that govern coupling of macroscopic motion to chemical reactions, as well as discovering other patterns of mechanochemical reactivity require complementary techniques, which permit a much more detailed characterization of reaction mechanisms and the distribution of force in reacting molecules than are achievable in SMFS or ultrasonication. A molecular force probe allows the specific pattern of molecular strain that is responsible for localized reactions in stretched polymers to be reproduced accurately in non-polymeric substrates using molecular design rather than atomistically intractable collective motions of millions of atoms comprising macroscopic motion. In this review, we highlight the necessary features of a useful molecular force probe and describe their realization in stiff stilbene macrocycles. We describe how studying these macrocycles using classical tools of physical organic chemistry has allowed detailed characterizations of mechanochemical reactivity, explain some of the most unexpected insights enabled by these probes, and speculate how they may guide the next stage of mechanochemistry.